IMPLEMENTATION OF THE CONCEPT SENTENCE LEARNING MODEL TO INCREASE STUDENTS' SOCIAL SCIENCE LEARNING OUTCOME IN STATE ELEMENTARY SCHOOL - Rahmadani Tanjung (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of the study is firstly to find out the students' learning outcomes in Social Science which has increased after the Concept Sentence Learning Model is applied. Secondly, it is to determine student learning activities in the learning process. This research is classroom action research. The subject of this study are Class V students of 162 Aek Marian State Elementary School with 14 male and 13 female students. The research instrument uses tests and field observations to obtain accurate data about the results and learning activities in the classroom. The results showed, firstly, there is an increase in learning outcomes in the pre-test from 0% to 59% in the cycle I which is included in the pass category with an average classical score of 67. Both results in the cycle II have a better increase in which the cycle II was 96% so that the result of the difference in the increase in cycle I and II is 37%. This increase in student learning outcomes proves that the application of the concept sentence learning model is effective in improving student learning outcomes.